THE INNOVATION MODEL OF TURBINE ENGINE COMPRESSOR TO SIMULATE THE PERFORMANCE IN OIL AND GAS INDUSTRY - Damianus Mario Ricky Fernando; Joko Waluyo (Airlangga Journal of Innovation Management, 2020)
ABSTRACTIn 1997s, East Kalimantan had several oil and gas fields that had reservoir pressure in the High-Pressure category. However, a few years later, the pressure continued to decrease until it reached Low Pressure, so the compressor is needed to produce high-pressure. In this study, an explanation of the process of making a turbine engine performance simulation model in 2019 is discussed and predicting turbine engine performance in the following years. This is important because the compressor is a vital tool in the oil and gas industry. Furthermore, it works continuously so that performance must be considered. In general, the simulation model equation consists of several parameters that exist in the Brayton cycle in the gas turbine in steady conditions. Simultaneous equation solving in simulation models using the Newton-Raphson method. The simulation results show that the performance of the Turbine Engine Compressor in 2019 has a net power of 20.58 MW with a cycle efficiency of 23.06%. This can be developed for plans for maintenance applications to improve efficiency changes. Keywords: simulation, Newton -Raphson, gas turbine, pressure, compressor ABSTRAK Pada tahun 1997, Kalimantan Timur memiliki beberapa ladang minyak dan gas yang memiliki tekanan reservoir dalam kategori tekanan tinggi. namun beberapa tahun kemudian, tekanan terus menurun hingga mencapai tekanan rendah, sehingga kompresor diperlukan untuk menghasilkan tekanan tinggi. Dalam penelitian ini, dibahas tentang proses pembuatan model simulasi kinerja mesin turbin pada tahun 2019 dan memprediksi performa mesin turbin di tahun-tahun berikutnya. Hal ini penting karena kompresor adalah alat vital dalam industri minyak dan gas. dan itu bekerja terus menerus sehingga kinerja harus diperhatikan. Secara umum, persamaan model simulasi terdiri dari beberapa parameter yang ada dalam siklus brayton di turbin gas dalam kondisi stabil. Penyelesaian persamaan simultan dalam model simulasi menggunakan metode newton-raphson. Hasil simulasi menunjukkan bahwa kinerja kompresor mesin turbin pada 2019 memiliki daya bersih 20,58 mw dengan efisiensi siklus 23,06%. Penelitian ini dapat dikembangkan untuk rencana aplikasi pemeliharaan untuk meningkatkan perubahan efisiensi. Kata kunci: simulasi, Newton-Raphson, turbin gas, tekanan, kompresor